The risk of intrapartum/neonatal mortality and morbidity following birth at 37 weeks of gestation: a nationwide cohort study. (24th April 2019) - Eskes, M; Ensing, S; Groenendaal, F; Abu‐Hanna, A; Ravelli, ACJ
Abstract : Objective: To assess intrapartum/neonatal mortality and morbidity risk in infants born at 37 weeks of gestation compared with infants born at 39–41 weeks of gestation. Design: Nationwide cohort study. Setting: The Netherlands. Population: A total of 755 198 women delivering at term of a singleton without congenital malformations during 2010–14. Methods: We used data from the national perinatal registry (PERINED). Analysis was performed with logistic regression and stratification for the way labour started and type of care. Main outcome measures: Intrapartum or neonatal mortality up to 28 days and adverse neonatal outcome (neonatal mortality, 5‐minute Apgar <7, and/or neonatal intensive care unit admission). Results: At 37 weeks of gestation intrapartum/neonatal mortality was 1.10‰ compared with 0.59‰ at 39–41 weeks ( P < 0.0001). Adjusted odds ratio (aOR) for 37 weeks compared with 39–41 weeks was 1.84 (95% CI) 1.39–2.44). Adverse neonatal outcome at 37 weeks was 21.4‰ compared with 12.04‰ at 39–41 weeks ( P < 0.0001) with an aOR 1.63 (95% CI 1.53–1.74). Spontaneous start of labour at 37 weeks of gestation was significantly associated with increased intrapartum/neonatal mortality with an aOR of 2.20 (95% CI 1.56–3.10), in both primary (midwifery‐led) care and specialist care. Neither induction of labour nor planned caesarean section showed increased intrapartum/neonatal mortality risk. Conclusions: Birth at 37 weeks of gestation is independently associated with a higher frequency of clinically relevant adverse perinatal outcomes than birth at 39–41 weeks. In particular, spontaneous start of labour at 37 weeks of gestation doubles the risk for intrapartum/neonatal mortality. Extra fetal monitoring is warranted. Tweetable abstract: Birth at 37 weeks of gestation gives markedly higher intrapartum/neonatal mortality risk than at 39–41 weeks, especially with spontaneous start of labour. Abstract : Tweetable abstract Birth at 37 weeks of gestation gives markedly higher intrapartum/neonatal mortality risk than at 39–41 weeks, especially with spontaneous start of labour.